Incidencia de la Ley del servicio civil en la gestión de los recursos humanos en la Municipalidad Provincial Sánchez Carrión periodo 2018 - Vera Paredes, Julissa Jovana (2019)
ABSTRACT The purpose of this research work was to establish the impact of the Law of Civil Service in the Management of Human Resources of the Provincial Municipality Sánchez Carrión period 2018, which was carried out through a study and analysis of the variables Law on Civil Service and Human Resources Management, the main objective of the investigation was to determine the relationship between the Civil Service Law and its impact on the Management of Human Resources in the Provincial Municipality Sánchez Carrión, period 2018; the survey was applied as an instrument for data collection; the population consisted of 497 servers, obtaining a representative sample equal to 115 servers; a survey questionnaire was applied to the sample obtained, in order to study the variables and the relationship between independent and dependent; the data collection instruments were validated by Cronbach's Alpha method, yielding an alpha of 0.855 for the Civil Service Act variable and 0.936 for the Human Resources Management variable; We reviewed previous research studies related to the subject investigated, in the same way the theories were oriented to the dimensions of both variables, the type of research is non-experimental, transversal and correlational, reaching the conclusion after processing the variables, the existence of a positive and significant correlation between both variables equal to 0.89 between both variables.